Robust path-following control for articulated heavy-duty vehicles - Barbosa, Filipe Marques; Marcos, Lucas Barbosa; da Silva, Maíra Martins; Terra, Marco Henrique; Grassi, Valdir (Control engineering practice, 2019)
Path following and lateral stability are crucial issues for autonomous vehicles. Moreover, these problems increase in complexity when handling articulated heavy-duty vehicles due to their poor manoeuvrability, large sizes and mass variation. In addition, uncertainties on mass may have the potential to significantly decrease the performance of the system, even to the point of destabilising it. These parametric variations must be taken into account during the design of the controller. However, robust control techniques usually require offline adjustment of auxiliary tuning parameters, which is not practical, leading to sub-optimal operation. Hence, this paper presents an approach to path-following and lateral control for autonomous articulated heavy-duty vehicles subject to parametric uncertainties by using a robust recursive regulator. The main advantage of the proposed controller is that it does not depend on the offline adjustment of tuning parameters. Parametric uncertainties were assumed to be on the payload, and an H∞ controller was used for performance comparison. The performance of both controllers is evaluated in a double lane-change manoeuvre. Simulation results showed that the proposed method had better performance in terms of robustness, lateral stability, driving smoothness and safety, which demonstrates that it is a very promising control technique for practical applications. •A Robust Linear Quadratic Regulator may be applied for path following problems.•Payload uncertainties can be considered in the proposed lateral control.•Smooth and robust autonomous driving was obtained for articulated heavy-duty vehicles.•In terms of robustness, the proposal has better performance than H∞ controller.